HIGHER EDUCATION: A CATALYST FOR CAPACITY BUILDING, ECONOMIC GROWTH AND NATIONAL DEVELOPMENT IN AFRICA - RUFAI, M.D; MOHAMMED, M.O.B.; YAHYA, L.O. (Advances in Social Sciences Research Journal, 2017)
There is increasing evidence that high levels of education in general, and of tertiary education in particular, are essential for the design and productive use of new technologies, while they also provide the foundations for any nation’s innovative capacity. Investment in higher education per se is a necessary but not a sufficient condition for development. As important as the investment made in higher education is, attention must be paid to the efficiency and effectiveness of that investment which includes ensuring that there are appropriate linkages with the labour market needs of the economy. As the race towards rapid and sustained improvement in knowledge and human resources gathers momentum, Nigeria and Africa must not be found wanting. Rather, formulation and implementation of a long-term growth strategy geared towards the development of human capital will address the current imbalances in the system and drive economic growth and national development. This paper reviews the impact of higher education on capacity building, economic growth and national development.